Pengaruh Panjang Talang Terhadap Produktivitas Air Tanaman Selada Kerinting dengan Sistem Irigasi NFT (Nutrient Film Technique) di PT. Momenta Agrikultura Lembang Bandung Barat - Agus Prasetyo; Muhammad Idrus; Surya Surya (Jurusan Teknologi Pertanian, 2015)
The research was conducted at the PT. Momenta Agrikultura Lembang West Bandung on February to April 2014. The objectives of the research were to determine amount of water used, production, and water productivity of salad (Lactuca sativa L.) with irrigation system nutrient film technique (NFT) with different lenght size of water chamfer. The result of the research showed that the size of length of water chamfer affected production and water productivity of salad. The amount of water used of salad on long size of water chamfer of 24 m with NFT was 23.52 l/plant nearly same with short size of water chamfer of 6 m was 24.24 l/plant. Salad production dan water productivity average by the using short size of gabel was higher compared to using long size of gabel. Salad production and water productivyti with using short size of water chamfer was average 217 g/plant and 8.95 kg/m3 water respectively but with using long size of water chamfer only 161g/plant and 6.85 kg/m3 nutrient. Keywords: length size of water chamfer, nutrient film technique (NFT), production, water productivyti and salad (Lactuca sativa L.)